Knowledge, Perceptions, Attitudes, and Health Seeking Behaviors Regarding HIV and Hepatitis B Co-Infection in Liberian Communities: A Community-Based Cross-Sectional Study - Prince L. Fully; Neima N. Candy; Aminata M. Sow; Alfreda B. Sandi, (International Journal of Preventive Medicine and Health (IJPMH), 2026)
Background: Although HIV and Hepatitis B virus (HBV) have similar transmission patterns in West Africa, little is known about how the population perceives HIV/HBV co-infection. This study examines people's attitudes, knowledge, and healthseeking habits in three Liberian communities about HIV/HBV coinfection. Methods: From December 2025 to January 2026, we conducted a community-based survey in Todee, St. Paul River, and Greater Monrovia. A standardized questionnaire, guided by the Health Belief Model and the Theory of Planned Behavior, was given to 40 individuals who were purposefully chosen. The analysis used descriptive statistics, chi-square testing, and logistic regression. Results: Only 65.0% of participants knew about Hepatitis B, and only 35.0% identified HIV/HBV co-infection, despite 95.0% being aware of HIV/AIDS. Educational level strongly influenced testing behaviours and knowledge outcomes (β = 0.42, p < 0.01). The major obstacle to healthcare access was reported as cost (40.0%), followed by fear of stigma (22.5%). Trust in healthcare practitioners was modest (mean 2.60/5), while felt stigma was high (3.52/5). The logistic model showed that HIV testing was substantially predicted by education (OR=1.8, 95% CI: 1.2-2.7) and healthcare trust (OR=1.5, 95% CI: 1.1-2.1). Conclusions: The Liberian population has significant information deficits about HIV/HBV co-infection. The findings highlight the need to remove financial barriers, eliminate stigma, train healthcare workers, and provide comprehensive health information. The cultural context of Liberia's post-conflict situation should inform these efforts.